The compatibility of properly managed productions forests with wildlife conservation in Borneo - Meijaard, E. (Universiti Malaysia, Sabah. Institute for Tropical Biology and Conservation, 2004)
This paper summarizes the detailed analysis of the relationship between ecological and life history characteristics of a selected number of Bornean vertebrates and their sensitivity to timber harvest and associated impacts. The data suggest that few species are negatively affected by the simple removal of commercial timber species. Associated impacts, however, such as increased hunting pressure in opened-up forest areas, increased erosion and soil compaction, slashing of lianas and ground cover vegetation, and fragmentation of once larger forest areas, can significantly reduce survival chances of wildlife populations in logged forests. Many of these negative impacts can be reduced by management interventions that do not necessarily reduce timber output from a forestry concession. Based on these findings, the authors provide recommendations for forestry managemnet that, if properly implemented, would increase the compatibility between logging and wildlife conservation.